The impact of sexually transmitted infections and inflammation in the female genital tract and blood on susceptibility to HIV-1 infection and disease progression - Masson, Lindi (Department of Clinical Laboratory Sciences, 2016)
Background. In sub-Saharan Africa, which has the highest prevalence of HIV-1 worldwide, most newHIV-1 infections occur by sexual transmission to women. Recent studies in non-human primates have demonstrated that pro-inflammatory cytokine production in the genital tract is necessary for immune cell recruitment and establishment of simian immunodeficiency virus (SIV) infection following vaginal inoculation. The aims of this study were to evaluate the relationships between inflammation in the female genital tract and (i) susceptibility to HIV-1 infection and (ii) subsequent disease progression in women who became infected. Additionally, genital inflammation was investigated as a mechanism for breakthrough HIV-1 infections in women who became infected even though they were using 1% tenofovir (TFV) microbicide. In the systemic compartment, the level of T cell activation and soluble markers of immune activation during HIV-1 infection are associated with disease outcome. Therefore, the relationships between plasma cytokine concentrations during early HIV-1 infection and disease progression were evaluated Methods. The participants of this study included 230 HIV-uninfected women from the CAPRISA 002cohort who were followed longitudinally for HIV-1 infection, 49 women who were enrolled during acuteHIV-1 infection and followed until 12 months post-infection and 166 HIV-uninfected women who were enrolled in the CAPRISA 004 1% TFV microbicide trial (62 of whom later became HIV-1-infected).Cytokine concentrations were measured in cervicovaginal lavage (CVL) and plasma samples from these women using Luminex and ELISA.